2010
DOI: 10.1007/s00464-010-1137-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed bleeding after endoscopic submucosal dissection for gastric neoplasm

Abstract: Risk factors for delayed bleeding, and the probable underlying mechanism involved, differed depending on the time elapsed between surgery and the bleeding episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
127
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 16 publications
10
127
2
Order By: Relevance
“…34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28]…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
See 3 more Smart Citations
“…34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28]…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
“…42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28][29][30][31]33,42,43,45 although 2 studies reported significantly higher PPB rates in hypertensive patients. 16,36 However, the adjusted OR was .67 in the latter study.…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
See 2 more Smart Citations
“…In gastric lesions an increased risk of bleeding has been reported when the lesions are located either in the middle or upper third of the stomach. Elderly (> 80 years), procedure time, size (≄ 40 mm) and endoscopist experience have been also associated with an increased risk of bleeding (95)(96)(97)(98).…”
Section: Hemorrhagementioning
confidence: 99%